Repeatability of nut yield in nutmeg - Jamdagni, P M Haldankar, G D Joshi, B P Patil, B M (Journal of Spices and Aromatic Crops, 2003)
An investigation was made to study the repeatability of nut yield in 34 nutmeg geneotypes under Maharashtra conditions. Remarkable variation for nut yield was recorded among genotypes. The mean sum of squares of variation between genotypes was predominantly larger than within genotypes. The magnitudes of repeatability were relatively low but the upper confidence limits were reasonably high. The study suggested that, in nutmeg yield recorded over a wider period is more consistent than single yield records at early stages. The genotypes N42, N72, N41 and N37 were found to have potential for nut yield.